Characterization and properties of high-temperature resistant structure adhesive based on novel toughened bismaleimide resins. (June 2021) - Wang, Daosheng; Xiong, Xuhai; Ren, Rong; Ma, Xinghua; Han, Anchang; Chen, Ping
A series of high-temperature resistant structural adhesives were prepared based on the copolymerization of 4, 4′-bismaleimidediphenylmethane (BDM) and 2, 2′-diallylbisphenol A (DABPA) together with a novel maleimide-capped polyetherimide containing cardo side groups (mPEI-C) as toughening agent. The chemical structure of the adhesives and their cured networks was characterized by Fourier transform infrared (FTIR) spectrometer. Their curing behavior and kinetics were analyzed using differential scanning calorimetry (DSC). The thermal properties, mechanical properties, bonding strength and moisture absorption behavior of the cured products were investigated by thermogravimetric analysis (TGA) and dynamic mechanical thermal analysis (DMA), etc. The modified resin system with mPEI-C exhibit similar curing behavior, and the apparent activation energy ( E a ) and reaction order ( n ) are equal to around 85.14 kJ/mol and 0.91, respectively. With increasing mPEI-C contends, the thermal stability is improved, the char yield is increased from 26.5% to 37.1%, and the glass transition temperatures have a slight decrease. The maximum flexural strength, impact strength and bonding strength are increased by 28.4%, 93.1% and 44.6%, respectively. The results of hygrothermal aging experiments exhibit the addition of mPEI-C has no obvious influence on the hygroscopicity of the modified resins.